2005
DOI: 10.1593/neo.05160
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Flat-Panel Volumetric CT in Morphologic, Functional Small Animal Imaging

Abstract: Noninvasive radiologic imaging has recently gained considerable interest in basic and preclinical research for monitoring disease progression and therapeutic efficacy. In this report, we introduce flat-panel volumetric computed tomography (fpVCT) as a powerful new tool for noninvasive imaging of different organ systems in preclinical research. The three-dimensional visualization that is achieved by isotropic high-resolution datasets is illustrated for the skeleton, chest, abdominal organs, and brain of mice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 30 publications
0
60
0
Order By: Relevance
“…16 FpVCT has already been described as a system for noninvasive imaging of different organ systems in preclinical research. 17 In combination with the administration of contrast agents, fpVCT allows accurate measurements of tumor volumes, vessel formation 18 and morphological changes within the tumor over time in subcutaneous and orthotopic tumor models in longitudinal studies. 19 FpVCT has also been used in monitoring skeletal structures, 20,21 including progression of osteolytic lesions, 22 as well as for the evaluation of therapy responses in vivo over time.…”
Section: Uiccmentioning
confidence: 99%
“…16 FpVCT has already been described as a system for noninvasive imaging of different organ systems in preclinical research. 17 In combination with the administration of contrast agents, fpVCT allows accurate measurements of tumor volumes, vessel formation 18 and morphological changes within the tumor over time in subcutaneous and orthotopic tumor models in longitudinal studies. 19 FpVCT has also been used in monitoring skeletal structures, 20,21 including progression of osteolytic lesions, 22 as well as for the evaluation of therapy responses in vivo over time.…”
Section: Uiccmentioning
confidence: 99%
“…HRCT findings regarding tumor size were validated by histopathological examination and correlated closely with necropsy findings (r=0.953; p<0.0001), suggesting that HRCT scanning may be used in the future to evaluate tumor growth and volume without euthanasia, thus avoiding time and resource-consuming procedures. Other recently published studies using experimental models 10,12,13 found the HRCT scanning technique to be an efficient tool for diagnosing lung nodules and to be less costly than magnetic resonance imaging 20 . The efficacy of HRCT scanning in the detection and measurement of tumors, as demonstrated by our study, makes it a suitable and non-invasive technique for diagnosing lung tumors, monitoring tumor growth and evaluating response to anticancer drugs in vivo in animals submitted to implantation with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Later Howard et al 8 and Johnston et al 7 improved the technique by using cervical tracheotomy for the insertion of an ultrafine intrabronchial catheter, thus making it possible to implant cells on the periphery of the pulmonary parenchyma. None of the studies above used computed tomography (CT) to detect the presence of lung tumors in the animals, although a few other and more recent experimental studies have reported using CT scans with small animals 10,12,13 . The objectives of this study were a) to develop a technically simple rat lung tumor model with intrabronchial implantation of cells of Walker's carcinosarcoma by cervical tracheotomy, and b) to diagnose tumors in vivo using high-resolution computed tomography (HRCT) with subsequent correlation of findings from necropsy and histopathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of micro structure function relationship of tissues and the designing tissue structures, including characterizing micro-architecture of tissue scaffolds by micro-CT has helped to design and fabricate of tailor-made tissue microstructures. Recent advances in micro-CT imaging [15], such as faster detectors, slip-ring technology, and dedicated rodent scanners, have made it possible to obtain high-resolution CT images with an isotropic spatial resolution of 0.075-0.15 mm [16][17]. Noninvasive imaging of ventilation has been shown to be sensitive to a variety of lung diseases [18].…”
Section: Non-invasive Imaging Data Acquisitionmentioning
confidence: 99%